Does Working Memory Impact Functional Outcomes in Individuals With ADHD: A Qualitative and Comprehensive Literature Review. Issue 13 (November 2019) - Fried, Ronna; Abrams, Jessica; Hall, Anna; Feinberg, Leah; Pope, Amanda; Biederman, Joseph
Objective: Working Memory (WM) is a domain of executive functioning often impaired in individuals with ADHD. Although assumed to cause difficulties across functioning, the scope of impairments from WM deficits in ADHD has not been investigated. The aim of this study was to examine outcomes associated with WM deficits in ADHD.Method: We conducted a search of the scientific literature on WM deficits, and Freedom From Distractibility (FFD), in ADHD using PubMed and PsycInfo databases.Results : The final sample included 11 controlled studies of WM/FFD deficits in ADHD with operationalized assessment of outcomes in academic, social, and emotional areas. WM assessment was divided into auditory-verbal memory (AVM) and spatial-visual memory (SWM). Seven studies examined WM deficits in academic functioning, eight studies assessed WM deficits in social functioning, and three assessed WM deficits in psychopathology.Conclusion: The majority of the literature suggests that WM deficits affect primarily academic functioning.